Determining Factors of Credit Risk for Conventional Banks Listed on the Indonesian Stock Exchange - Alwaini, Helmy; Fadhila, Rakha; Herlambang, Prio; Lestari, Henny (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Credit risk is an important factor affecting the financial stability of banks. Keeping credit risk under control is critical to maintaining the bank's cash flow. This study examines various profitability, microeconomic, and macroeconomic indicators that affect bank credit risk. This study uses a data set of 44 banks from 2018 to 2022 listed on the Indonesian Stock Exchange and uses a panel data modeling approach to account for variations in risk-taking behavior. The results show a statistically significant negative relationship between return on equity and credit risk (non-performing loans). This finding is consistent in the fixed effect, random effect, and common effect methods, with a significance of 5 percent (P value <0.05). which indicates that the level of credit risk increases with a decrease in return on equity, and further findings show that net interest margin has a positive effect on credit risk (non-performing loans) and microeconomics such as size, efficiency, capitalization, bank diversification have a positive influence on credit risk (non-performing loans). And for macroeconomic variables, it shows a negative influence on credit risk (non-performing loans) where if there is an increase in inflation or a decrease in GDP, it will affect the increase in credit risk.